Construction and Demolition Waste (C&DW) Management - Neupane, Priyeshchandra; Pokhrel, Rajib (LTU Journal of Advanced Computing & Engineering, 2026)
Construction and Demolition Waste (C&DW) constitutes a substantial fraction of the global solid waste stream and presents a critical impediment to sustainable development. This paper critically examines prevailing practices, emerging trends, and pressing concerns in C&DW management worldwide, with particular emphasis on Asia and Nepal. Established practices such as recycling, reuse, material recovery, selective demolition, and the integration of digital technologies including Building Information Modeling (BIM) and artificial intelligence for waste sorting are reviewed in relation to their efficacy and scalability. While developed economies have advanced integrated systems underpinned by stringent regulatory frameworks and market-based instruments, most developing regions remain constrained by fragile policy environments, financial limitations, technical deficits, and a reliance on informal waste economies. The circular economy (CE) paradigm offers a transformative framework to reconceptualize C&DW as a secondary resource, reduce dependence on virgin materials, and diminish the sector’s carbon footprint. By reinforcing lifecycle awareness, material efficiency, and innovative business models, CE strategies align directly with broader global sustainability agendas. However, implementation remains highly uneven, largely due to entrenched systemic, economic, and institutional barriers. Overcoming these challenges necessitates targeted investment, adaptive policy reform, inclusive stakeholder engagement, and accelerated technological innovation. Collectively, these measures are essential for advancing C&DW management toward a circular trajectory and unlocking its potential as a catalyst for sustainable growth within the construction sector.